ANALISIS POTENSI ENERGI DI DESA WUKIRSARI KECAMATAN IMOGIRI KABUPATEN BANTUL PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Dengkeng, Kobango, Giriloyo, and Nogosari II are places in the Wukirsari village which experience water scarcity. Water supply system (WSS) is proposed to fulfill water for 1,088 persons. The WSS need energy for pumping amount 88.47 kWh per day. Based on Atmospheric Data Science's datas, obtained that the average of wind velocity in Imogiri is 4.20 meters/second and 50.00 meters in height above the sea level. The standard of wind velocity to build wind power generation is must more than 3.00 meter/ second so enable to design in another turbine height. By region coefficient (a) 0.30, is obtained turbine height alternative 18.17 - 50.00 meters in range. By varied wind velocity base on that range obtained wind velocity average amount 3.70 meters/second and 32.17 - 33.17 meters in height range. Based on WSS's lifetime and wind specific mass, obtained power per wide unit 21.06 W/m² and energy 0.02 kWh/m² each day.